Image cipher applications using the elliptical curve and chaos - Silva-García, Victor Manuel; Flores-Carapia, Rolando; Rentería-Márquez, Carlos; Luna-Benoso, Bejamín; Chimal-Eguía, Juan Carlos (Zielona Góra: Uniwersytet Zielonogórski)
A novel symmetric cryptosystem of the substitution permutation network type is presented for image encryption in 14 rounds. An algorithm is developed to generate 15 keys to encrypt images where each key is the image size. These keys are calculated using an elliptic curve with a constant zero value. The proposed curve is non-singular, non-supersingular, nor trace one.
Keywords: elliptic curve; chaos; entropy; discrete Fourier transform; image ciphering